Ts. Dr. Noorlisa develops Safe Thorium Purification Model from Rare Earth Waste - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 18 August 2025 – The extraction of rare earth elements (REEs) from lanthanide concentrates in Malaysia generates radioactive waste known as Water Leach Purification (WLP). This waste contains thorium at levels of about 6.7 Bq/g—far exceeding the safe limit of 1 Bq/g.